Reconsidering longstanding assumptions about the role of medial prefrontal cortex (MPFC) in social evaluation - Jessica E. Koski; Jacie R. McHaney; Anastasia E. Rigney; Jennifer S. Beer (NeuroImage, 2020)
The psychological nature of the association between MPFC modulation and social evaluation remains poorly understood. Despite confounds, small samples, and mixed results in existing research, MPFC activation is often interpreted as a reflection of socioemotional association and/or perceived similarity between the self and an evaluation target. The present research addressed issues from the existing literature by examining whether MPFC is modulated by (a) socioemotional associations unconfounded by previous knowledge (memory effects (Study 1, N = 48), repetition suppression (Study 2, N = 43), multi-voxel pattern analysis (Study 1 & 2)) and (b) perceived similarity to self (Study 2). MPFC was modulated by self-reference and trait-relevance, but there was not significant empirical support for the interpretation that MPFC modulation reflects socioemotional association or perceived similarity. These findings highlight the weak basis for prevailing assumptions about the psychological significance of MPFC in social evaluation and the need for studies which test multiple mechanisms.